Hunting for hidden gold - Dixon, Franklin W. (Dixon, Franklin W. Hardy boys mystery stories, 1991)
Timber wolves, a Rocky Mountain blizzard, and a mine cave-in are only a few of the perils Frank and Joe Hardy encounter during their search for the principal members of a notorious gang responsible for a payroll robbery.